Clays Can Decrease Gaseous Nutrient Losses from Soil‐Applied Livestock Manures. Issue 2 (1st March 2016) - Pratt, Chris; Redding, Matthew; Hill, Jaye; Brown, Grant; Westermann, Maren
Abstract : Clays could underpin a viable agricultural greenhouse gas (GHG) abatement technology given their affinity for nitrogen and carbon compounds. We provide the first investigation into the efficacy of clays to decrease agricultural nitrogen GHG emissions (i.e., N2 O and NH3 ). Via laboratory experiments using an automated closed‐vessel analysis system, we tested the capacity of two clays (vermiculite and bentonite) to decrease N2 O and NH3 emissions and organic carbon losses from livestock manures (beef, pig, poultry, and egg layer) incorporated into an agricultural soil. Clay addition levels varied, with a maximum of 1:1 to manure (dry weight). Cumulative gas emissions were modeled using the biological logistic function, with 15 of 16 treatments successfully fitted ( P < 0.05) by this model. When assessing all of the manures together, NH3 emissions were lower (×2) at the highest clay addition level compared with no clay addition, but this difference was not significant ( P = 0.17). Nitrous oxide emissions were significantly lower (×3; P < 0.05) at the highest clay addition level compared with no clay addition. When assessing manures individually, we observed generally decreasing trends in NH3 and N2 O emissions with increasing clay addition, albeit with widely varying statistical significance between manure types. Most of the treatments also showed strong evidence of increased C retention with increasing clay additions, with up to 10 times more carbon retained in treatments containing clay compared with treatments containing no clay. This preliminary assessment of the efficacy of clays to mitigate agricultural GHG emissions indicates strong promise. Core Ideas: Technologies to mitigate agricultural GHG emissions are in demand. We tested the ability of clays to abate GHG emissions from soil + manure mixes. To our knowledge, this is the first study of its kind. The clays showed strong promise to decrease N emissions by as much as 90%. The clays also showed potential to boost C retention in soil + manure systems.